Adding fat and/or sodium bicarbonate to steer finishing rations that contain wheat - Brethour, J.R.; Lee, B.; Riley, Jack G. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Adding .6 pound fat or .22 pound sodium bicarbonate (soda) to finishing rations containing rolled wheat significantly improved performance and appeared to increase the substitution value of wheat. Both fat and soda increased feed intake. The improved gains from adding fat corresponded to increased energy intake. However, soda seemed to enhance nutrient utilization. There was more response to fat when we fed 100 percent vs. 50 percent wheat, but feeding 100 percent wheat depressed performance, with or without fat, to unsatisfactory levels.
Keywords: Beef; Fat; Sodium bicarbonate; Steer; Wheat